Psychosocial factors and health services utilization in Fibromyalgia: a review - Ana Lledó Boyer (Universidad de San Buenaventura, 2011)
Studies on the socioeconomic impact of fibromyalgia (FM) have shown the high health services use done by these patients. These data indicate the challenge of dealing with these people, their treatment and rehabilitation, as well as the need of changes in actions and implementation of cost-effective approaches. In this study we reviewed the literature on the health care use behavior in FM. The data shows that the emotional state and catastrophizing are relevant factors in the onset of seeking health care, and within the system, higher self-efficacy, attributions of symptoms to external factors, the perception of good health and lower comorbidity is associated with less use.